Nigeria : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The Nigerian economy remained strong, with a non-oil real GDP of 8.3 percent and an overall real GDP of 6.7 percent. A modest fiscal consolidation took place in 2011 as a response to the substantial monetary tightening by the Central Bank of Nigeria and moderation of food prices. Banks showed continued improvement in financial stability. Executive Directors commended the authorities for countercyclical policies. However, they emphasized the need for policies that safeguard macroeconomic stability and ensure inclusive growth.